Increased lymphocyte apoptosis in mouse models of colitis upon ABT-737 treatment is dependent upon BIM expression - Lutz, C (Clin Exp Immunol, 2015)
Exaggerated activation of lymphocytes contributes to the pathogenesis of inflammatory bowel disease (IBD). Medical therapies are linked to the BCL-2 family-mediated apoptosis. Imbalance in BCL-2 family proteins may cause failure in therapeutic responses. We investigated the role of BCL-2 inhibitor ABT-737 for lymphocyte apoptosis in mice under inflammatory conditions. B.6129P2-interleukin (IL)-10(tm1Cgn)/J (IL-10(−/−)) weighing 25–30 g with ongoing colitis were used. Fifty mg/kg/day ABT-737 was injected intraperitoneally (i.p.). Haematological analyses were performed with an ADVIA 2120 flow cytometer and mass cytometry with a CyTOF 2. Following i.p. administration, ABT-737 was detected in both spontaneous and acute colitis in peripheral blood (PBL) and colon tissue. Treatment led to lymphopenia. CD4(+)CD44(+)CD62L(+) central memory and CD8(+), CD44(+) CD62L(−) central memory T cells were decreased in PBL upon ABT-737 compared to vehicle-receiving controls. Increased apoptosis upon ABT-737 was determined in blood lymphocytes, splenocytes and Peyer’s patches and was accompanied by a decrease in TNF and IL-1B. ABT-737 positively altered the colonic mucosa and ameliorated inflammation, as shown by colonoscopy, histology and colon length. A decreased BIM/BCL-2 ratio or absence of BIM in both Bim(−)(/)(−) and Il10(−)(/)(−) × Bim(−)(/)(−) impeded the protective effect of ABT-737. The BIM/BCL-2 ratio decreased with age and during the course of treatment. Thus, long-term treatment resulted in adapted TNF levels and macroscopic mucosal damage. ABT-737 was efficacious in diminishing lymphocytes and ameliorating colitis in a BIM-dependent manner. Regulation of inappropriate survival of lymphocytes by ABT-737 may provide a therapeutic strategy in IBD.